The Merry Men, and Other Tales and Fables - Stevenson, Robert Louis, 1850-1894 (Salt Lake City, UT : Project Gutenberg, 1995)
"The Merry Men, and Other Tales and Fables" by Robert Louis Stevenson is a collection of short stories written in the late 19th century. The opening story, "The Merry Men," introduces readers to a richly atmospheric setting in the Scottish Hebrides, where themes of isolation, superstition, and the sea's treachery play a significant role. The protagonist, Charles Darnaway, discovers a family legacy tied to shipwrecks and hidden treasures, which intertwines with his feelings for his cousin Mary Ellen and their shared family history. The opening of "The Merry Men" sets the scene with Charles traveling to Aros, a remote island owned by his uncle, Gordon Darnaway. He reflects on family history, local legends, and the mysterious allure of the sea, particularly the treacherous Merry Men, a group of dangerous waves notorious for shipwrecks. As he arrives, he observes changes brought about by a recent shipwreck and the uneasy atmosphere surrounding his uncle and Mary Ellen. A sense of foreboding looms as he learns of surfacing dreams of treasure tied to an Armada ship that was lost long ago, prompting moral reflections on the implications of greed, loss, and the supernatural that seem to haunt Aros and its inhabitants. (This is an automatically generated summary.)
The merry men -- Will o' the mill -- Markheim -- Thrawn Janet -- Olalla -- The treasure of Franchard.
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Merry_Men_and_Other_Tales_and_Fables
Release date is 1995-10-01
David Price
Keywords: Boys -- Fiction; Treasure troves -- Fiction; Paranormal fiction; Great Britain -- History -- 19th century -- Fiction